Female Students’ Knowledge and Behavior in Relation to Breast Examination - Damayanti S, Febrina; Budiawan, Mawar Julia; Banggapian, Onying; Cathryne, Joice; Sihaloho, Shinta Marina Josephina Putri (Jurnal Keperawatan Priority, 2024)
Further research will be conducted on the factors that influence the realization examination. Breast cancer is a major global health problem and the highest cause of death among women because many women who suffer from breast cancer are found in the final stage, making it difficult to cure. Breast self-examination is a preventive measure that is done independently to detect early changes in the breast, but even though it can be done by yourself, many women rarely do it. Based on an initial survey of 20 female students, 11 did not know the meaning of breast self-examination, 15 did not know how to do breast self-examination, and 3 had a family history of breast cancer. The purpose of this study was to determine the relationship between knowledge and behavior of female students regarding breast self-examination at the Faculty of Economics and Business at one of the universities in Banten. Purposive sampling is the sampling strategy utilized in this study, which employs cross-sectional sampling with a sample of 88 female students. The Chi-Square test results for the data analysis revealed a p-value of 0.272 (p < 0.05). In summary, there is no correlation between knowledge and the behavior of female students in breast self-examination. Further research will be conducted to determine the factors that influence breast self-examination.